Disruption of STAT6 Signal Promotes Cardiac Fibrosis Through the Mobilization and Transformation of CD11b+ Immature Myeloid Cells - Zhang, Weiwei; Zhu, Baoling; Ding, Suling; Wang, Xiangfei; Wu, Jian; Zhu, Xiaowei; Zou, Yunzeng; Ge, Junbo; Tong, Minghong; Yang, Xiangdong (Frontiers in Physiology, 2020)
The roles of STAT6 signal in allergy, immune regulation, tumorigenesis, and renal fibrosis have been documented. However, the function and mechanism of STAT6 signal in sympathetic overactivation-induced cardiac fibrosis have not been fully elucidated. This study explores the novel role of STAT6 signal in isoproterenol (ISO)-induced cardiac fibrosis through the regulation of inflammatory response and the differentiation of macrophages from immature myeloid cells. The expression levels of STAT6, β1-AR, and inflammatory factors in CD11b+ myeloid cells were analyzed with a microarray study. The levels of IL-6 and TGF-β1 in the CD11b+ myeloid cells-derived macrophages were detected with RT-PCR. STAT6-KO and WT mice were used to establish a murine cardiac fibrosis model. Cardiac fibroblasts were isolated from the hearts of newborn mice, and STAT6 expression was measured by western blotting and RT-PCR. α-SMA expression was detected by immunofluorescence and immunohistochemistry staining. Cardiac function and pathological characteristics were examined by echocardiography and immunohistochemistry staining, respectively. Immunohistochemistry staining with anti-CD11b was performed to detect the infiltration of CD11b+ myeloid cells in heart tissue. Flow cytometry analysis was used to measure the percentages of CD11b+ myeloid cells and CD11b+Ly6C+ macrophages in the peripheral blood. Results showed that STAT6 was highly expressed in CD11b+ myeloid cells located in injured hearts, and STAT6 expression in cardiac fibroblasts was down-regulated after ISO treatment. STAT6 deficiency further aggravated ISO-induced increased expression of α-SMA in cardiac fibroblasts, myocardial fibrosis and cardiac dysfunction. The activation of ISO/β1-AR signal aggravated cardiac inflammatory infiltration, promoted CD11b+ myeloid cell mobilization and enhanced CD11b+Ly6C+/low macrophage differentiation, which was further exacerbated by STAT6 deficiency. Furthermore, β1-AR mRNA expression significantly increased in splenic CD11b+ myeloid cells compared to their bone marrow-derived controls, and STAT6 deficiency promoted β1-AR expression in an MI-induced sensitive cardiac fibrosis mouse model. The spleen-derived CD11b+ myeloid cells of STAT6-KO mice produced more IL-1α, IL-18 and TGF-β than their WT counterparts. Taken together, these results suggest that STAT6 signal plays a critical role in ISO-induced β1-AR overactivation and systemic inflammatory cascades, contributing to cardiac fibrogenesis. STAT6 should be a promising cardioprotective target against myocardial fibrosis and heart failure after β1-AR overactivation-induced myocardial injury.